Production Utilized Capacity Improvement Proposal Using Lean Six Sigma: A Case Study At Plastic Injection Process PT Indonesia Trc Industry - Fikka Ruhaiya; Gatot Yudoko; Pennoh Philips Kembaren (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The plastic injection production process often faces problems with products that do not meet quality standards (not achieved), which causes an increase in defect rates, decreased efficiency and failure to achieve production targets. This study aims to identify the main causes of these problems and apply the Lean Six Sigma method to improve productivity. Pareto analysis shows that most of the main causes of plastic injection production activities are caused by machine trouble. Through the DMAIC (Define Measure, Analyze, Improve, Control) approach, it was found that the factors causing machine trouble were influenced by unscheduled machine maintenance, temperature settings, pressure, and cycle time. In addition, the lack of adequate training for operators also plays a role in worsening molding quality. The improvement plan implemented includes the use of monitoring sensors such as the Internet of Things with the Kaizen approach.